Repurposing face mask waste to construct floating photothermal evaporator for autonomous solar ocean farming - Guo, Shuai; Zhang, Yaoxin; Qu, Hao; Li, Meng; Zhang, Songlin; Yang, Jiachen; Zhang, Xueping; Tan, Swee Ching (EcoMat (Beijing, China), 2022)
Plastic waste caused by the extensive usage of face masks during COVID‐19 pandemic has become a severe threat to natural environment and ecosystem. Herein, an eco‐friendly approach to repurpose face mask waste for clean water production via solar thermal evaporation is proposed. By taking advantage of its interwind structure, face mask holds the promise to be an ideal candidate material for constructing photothermal evaporator. In‐situ surface modifications are performed successively with polyvinyl alcohol and polypyrrole to improve its wettability and solar absorption (97%). The obtained face mask‐based evaporator achieves significantly enhanced solar efficiency (91.5%) and long‐term salt‐rejection stability. The harvested clean water befits plant growing to enable farming on sea surface. A floating photothermal evaporation prototype is then developed to demonstrate autonomous solar ocean farming, with plants successfully cultivated over time. As such, the proposed strategy provides a promising solution towards ecological sustainability by tapping multiple benefits. This work presents an eco‐friendly way to recycle large amount of wasted face masks into solar absorbers for clean water production. A prototype of floating farm is further demonstrated, using recycled face mask to convert abundant seawater into portable water for plants irrigation. Plants can be well thrived, giving a promising solution to land soil crisis and polymer white pollution.